Avaliação do desempenho ambiental do aproveitamento do biogás em fecularias de mandioca no estado do Paraná: um estudo de casos múltiplos - Guimarães, Celso Eduardo (2014)
For the production of starch and cassava flour occurs the steps of washing, peeling, grating and pressing in order to obtain the product. These phases generate large amounts of waste with high content of organic matter and toxic components, such as the yellow water resulting from pressing cassava, known as manipueira. Usually these residues are treated in settling ponds, where the degradation occurs by anaerobic processes, generating biogas which is released into the atmosphere. The main constituents of biogas are methane (CH4) and carbon dioxide (CO2). In an initiative by companies from the state of Paraná, Brazil, a new technology has been installed to turn the lagoons in digesters to capture methane from the perspective of an alternative for the treatment of waste and promotion of environmental innovation. However, this technology is new in this kind of industry, still requiring evaluation of their technical, economic and environmental benefits. Within this context, the following research question can be presented: what advantages and disadvantages of the use of biogas the technology brings in the environmental point of view and how to characterize them and evaluate them? This study evaluated the environmental performance in three industries, applying the methodology of multiple case study. In order to support the collection and interpretation of data processing, it was selected environmental performance indicators from the framework for sustainability reporting GRI, related to aspects of material consumption, air emissions, water consumption, energy consumption, emission and effluent. As a result of the application of these indicators, some positive results, such as reduction consumption of fuel wood and of the atmospheric emissions of greenhouse gas (GHG) were observed. Research has shown, using the numbers presented on the indicators evaluated, that the use of biogas in the agribusiness sector is a kind of promising initiative by the points of views economically and environmentally, with significant positive practical results, noting that one of the companies surveyed had a decrease in the consumption of firewood in the order of 95%. Another was less considerable, saving half of the wood with the use of biogas. In all cases, however, there was considerable improvement in performance, with a reduction of costs production and of the emissions of air pollutants, especially in relation to GHGs. In this way, the research contributes to a better understanding of technology and a possible fomentation to use it.